2018
DOI: 10.15744/2455-7641.4.104
|View full text |Cite
|
Sign up to set email alerts
|

Induce Hyperlipidemia in Rats Using High Fat Diet Investigating Blood Lipid and Histopathology

Abstract: The experiment was conducted to investigate the effect of induced hyperlipidemia in SD rats fed with high fat diet (HFD) for 7 weeks on blood lipid profile and possible pathological changes in liver, stomach, intestine, heart, spleen, lung and kidney. There were significant differences in most rats which induced hyperlipidemia throughout the experimental period with the blood lipid levels and histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…As a reported example, a study on Wistar rats established that several weeks into a regimen of HFD lead to obesity and dyslipidemia (Rosnah et al, 2022). Another study (Karam, Ma, Yang, & Li, 2018) on the same species of rats as in the current study (Sprague-Dawley rats) has also reported significant increase in hyperlipidemia biomarkers after only 7 weeks of consumption of HFD with the following macronutrients (41.5% lipids, 40.2% carbohydrates, and 18.3% proteins (kcal)).…”
Section: Discussionsupporting
confidence: 54%
“…As a reported example, a study on Wistar rats established that several weeks into a regimen of HFD lead to obesity and dyslipidemia (Rosnah et al, 2022). Another study (Karam, Ma, Yang, & Li, 2018) on the same species of rats as in the current study (Sprague-Dawley rats) has also reported significant increase in hyperlipidemia biomarkers after only 7 weeks of consumption of HFD with the following macronutrients (41.5% lipids, 40.2% carbohydrates, and 18.3% proteins (kcal)).…”
Section: Discussionsupporting
confidence: 54%
“…According to sampling and trimming procedures, the pancreatic tissue was dehydrated and paraffinized [26]. In an automatic procedure, a section of about 4µm was stained by conventional hematoxylin and eosin (H&E) stains [27].…”
Section: Histological Examinationmentioning
confidence: 99%
“…A total of forty-five rats were randomly divided into nine groups of five each. Hyperlipidemia was induced in rats by feeding them with high-fat diet as done by Karam et al [23] with modification in the feeding duration (35 days). After the 35 days feeding exercise, blood sample were collected from their tails after immersed in water bath at 45 o C for 5 min to make the blood vessel swell in order to get the desire volume (1-1.5 ml).…”
Section: Experimental Designmentioning
confidence: 99%